Moving Beyond the Native-Speaker Bias in the Analysis of Variable Gender Marking - Gudmestad, Aarnes; Edmonds, Amanda; Metzger, Thomas (Frontiers in Communication, 2021)
In the current study, we respond to calls for reform in second language acquisition that center on the field’s preoccupation with native-speaker and prescriptive targets as a benchmark for additional-language learning. In order to address these concerns, we examine the use and development of grammatical gender marking in additional-language Spanish in a prescriptive-independent manner. Specifically, we depart from previous analyses that have centered on accuracy and targetlikeness and we shift the object of analysis to the linguistic forms (i.e., feminine and masculine modifiers) that additional-language participants use. We adopt a variationist approach to explain how participants vary their use of modifier gender and how this use changes longitudinally. We argue that such an approach to studying additional languages allows us to offer new insights about the acquisition of grammatical gender marking in additional-language Spanish. We end by critically reflecting on some of the challenges that we encountered in trying to integrate this paradigm shift into the examination of a well-studied grammatical structure.